2013
DOI: 10.1103/physrevlett.110.227402
|View full text |Cite
|
Sign up to set email alerts
|

Measurement of Filling-Factor-Dependent Magnetophonon Resonances in Graphene Using Raman Spectroscopy

Abstract: We perform polarization-resolved Raman spectroscopy on graphene in magnetic fields up to 45T. This reveals a filling-factor-dependent, multicomponent anticrossing structure of the Raman G peak, resulting from magnetophonon resonances between magnetoexcitons and E2g phonons. This is explained with a model of Raman scattering taking into account the effects of spatially inhomogeneous carrier densities and strain. Random fluctuations of strain-induced pseudomagnetic fields lead to increased scattering intensity i… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
61
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(70 citation statements)
references
References 35 publications
8
61
1
Order By: Relevance
“…[7][8][9][10][11] Besides the use of Raman spectroscopy for the analysis of e-ph coupling in graphene, Raman measurements of phonon excitation can be used to probe strain in graphene. [12][13][14] Splitting of the G peak by strain has already been observed experimentally, [15][16][17][18][19] in agreement with density functional theory (DFT) modeling of the Grüneisen parameter.…”
mentioning
confidence: 99%
“…[7][8][9][10][11] Besides the use of Raman spectroscopy for the analysis of e-ph coupling in graphene, Raman measurements of phonon excitation can be used to probe strain in graphene. [12][13][14] Splitting of the G peak by strain has already been observed experimentally, [15][16][17][18][19] in agreement with density functional theory (DFT) modeling of the Grüneisen parameter.…”
mentioning
confidence: 99%
“…This interaction manifests itself through the magneto-phonon resonance, a series of avoided crossings between the phonon mode and the electronic excitation spectrum each time a ∆|n| = ±1 inter Landau excitation is tuned to the phonon energy. [9][10][11][12][13][14] Magneto-phonon resonance has also been observed in multi-layer graphene specimens, 15 in bulk graphite for both H and K point carriers 16,17 and is now a tool to study the electron-phonon interaction and to perform the Landau level spectroscopy of unknown systems. At the resonance, the splitting energy depends on the effective oscillator strength of the electronic excitation which is determined by the strength of the magnetic field and by the occupancy of the initial and final Landau levels implied in the excitation.…”
Section: Abstract: Graphene Raman Spectroscopy Magneto-phonon Resonmentioning
confidence: 99%
“…Up to now, most magneto-Raman scattering experiments have been performed on graphene specimens with a fixed carrier density n s . 13,14 Recently, Remi et al 18 reported on unpolarized Raman scattering experiments on a gated graphene sample, at B = 12.6 T, in the non-resonant regime.…”
Section: Abstract: Graphene Raman Spectroscopy Magneto-phonon Resonmentioning
confidence: 99%
“…This dependence was proposed as a probe to measure the strength of the electron-phonon coupling and to resolve the phonon polarization 10 . Several magneto-Raman measurements have given evidence of the predicted fine structure properties of the MPR of the graphene G band 5,[11][12][13][14][15][16][17] and in particular its filling factor and light polarization dependences. The most pronounced effect of MPR was found, at high magnetic field, for the inter-LL transitions 0 → 1 and −1 → 0 10,15,17 .…”
Section: Introductionmentioning
confidence: 99%